2020
DOI: 10.22271/phyto.2020.v9.i3ah.11615
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of pigeonpea [Cajanus cajan (L.) Millsp.] Under cold stress conditions

Abstract: In this study, one forty five pigeonpea genotypes were assessed for cold tolerant associated traits. For evaluation of these traits, principal component and correlation analyses were applied to select desirable parents that can be further exploited in future breeding programmes. Correlation analysis revealed pods per plant, biomass, 100-seed weight, harvest index and osmolarity had positive and significant associations, while the membrane injury index had a significant negative correlation with yield at cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…This graph indicated that initial plant stand followed by final plant stand, yield (kg ha -1 ) and number of pods plant -1 contributed maximum to the total divergence [ Fig 2]. Behera et al [17], Alagupalamuthirsolai et al [18] also validated their result through biplot analysis in rice.…”
Section: Scatter Plot and Biplot Pca Analysismentioning
confidence: 87%
“…This graph indicated that initial plant stand followed by final plant stand, yield (kg ha -1 ) and number of pods plant -1 contributed maximum to the total divergence [ Fig 2]. Behera et al [17], Alagupalamuthirsolai et al [18] also validated their result through biplot analysis in rice.…”
Section: Scatter Plot and Biplot Pca Analysismentioning
confidence: 87%